(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The present study aims to evaluate the assessment of educational technology in ELT on the reading skills of students. The experimental approach was adopted by the research. The researchers prepared a multimedia kit with 10 reading ability components such as phonemes, segmenting, substituting, vowels consonants, prefixes suffixes, nouns, prepositions, verbs, articles and SVO pattern for reading skill measurement. The multimedia system was checked by 30 5th grade students from Kolkata, West Bengal. There were 15 control groups out of 30 students and 15 were experimental groups. Treatment with the conventional chalk and talk approach was given to the control group and multimedia package treatment was given to the experimental group. There were 10 materials in a kit and each material was checked each day. To assess their academic performance, the researchers performed pre-tests and post-tests.